A simple bedside approach to therapeutic goals achievement during the management of deceased organ donors – An adapted version of the "VIP" approach. Issue 2 (8th January 2016) - Westphal, Glauco Adrieno
Abstract: The disproportion between the supply and demand of transplant organs could be alleviated by improving the quality of clinical management of deceased potential donors. As a large number of donor losses by cardiac arrest occur due to hemodynamic instability, without instituting all essential maintenance measures, it is likely that the application of simplified potential donor maintenance protocols will help to decrease potential donor losses and increase the supply of organs for transplantation. The Ventilation, Infusion and Pumping (VIP) strategy is a mnemonic method that brings together key aspects of the restoration of oxygen delivery to tissues during hemodynamic instability: adequate mechanical Ventilation, volume Infusion and evaluation of heart Pump effectiveness. The inclusion of the additional initials, "P" and "S, " refers to Pharmacological treatment and Specificities involved in the etiology of shock. The use of simplified care standards can assist in adhering to essential potential donor management measures. Therefore, using a simplified method as the adapted VIP approach can contribute to improving management standards of potential organ donors and increasing the supply of organs for transplantation.